Nefrectomia total unilateral em cachorro-do-mato (Cerdocyon thous) - Piccoli, Ronaldo José; Thomazoni, Dhyego; Druziani, Juliana Teixeira; Hamamura, Márcio; de Carvalho, Anderson Luiz (Acta Scientiae Veterinariae, 2017)
Background: The loss of natural habitats associated with the development of humanity resulted in the need for longer trips and greater interaction with highways by some animal species. Vehicle collision with animals is one of the main factors of pressure over wild animal populations in Brazil; veterinary surgery can play an important role for the recovery of these patients. The lesions commonly seen in animals hit by vehicles may comprise skin lesions, central nervous system injuries, intrathoracic and intra-abdominal complications, among which renal lesions are included. The aim of this work is to report the use of a total nephrectomy technique in a crab-eating fox. Case: A female, adult, 5-kg crab-eating fox (Cerdocyon thous Linnaeus, 1766) was received for emergency care at the Veterinary Hospital of Universidade Federal do Paraná at Palotina. The patient had been struck by a vehicle at a local highway, was unconscious, and exhibited signs of blood loss such as hypothermia, hypotension, and pale mucous membranes. As the clinical evaluation was performed, the patient was stabilized with pain management, correction of hypovolemia and hypothermia, and oxygen therapy. Blood samples were taken in case of the need for preoperative tests. Subsequently, the animal was submitted to the diagnostic imaging section to investigate possible injuries. No chemical restraint was necessary for the procedures. Radiography examination revealed loss of intra-abdominal contrast, which was confirmed to be free fluid on ultrasound examination. Immediately after imaging examination, the animal was taken to the surgical room for exploratory laparotomy. The surgical incision, which was performed over the linea alba, extended from the xiphoid process to the pubis. During surgery, free fluid was confirmed to be diffuse bloody fluid, which was observed in the abdomen; there was absence of lesions in all organs except the right kidney, which revealed clots and lacerations to the capsule, cortex, and medulla, resulting in poor viability of the organ. The condition required removal of the organ, which was performed with the conventional technique described for domestic animals. During the nephrectomy surgical procedure, the patient exhibited severe hypotension with the need of compensatory measures such as intravenous administration of crystalloid and colloid solutions, and vasoactive drugs, which were maintained during the period of surgery. Postoperative care included administration of analgesics and anti-inflammatory drugs for three days, and antibiotics for seven days. Hematological and renal profiles as well as ultrasound examinations were used for monitoring of clinical evolution. The patient was kept in isolation to avoid behavioral stress during hospital stay. Discussion: In this case, the importance of ultrasound diagnosis and viability of the nephrectomy technique were established for the specimen, which was returned to its natural habitat eighteen days after the vehicle collision, after authorization from the local environmental agency. Immediate care of a wild animal that suffers trauma is an important factor to increase success rate for recovery of fauna threatened by vehicle collisions. Early diagnosis associated with the employment of surgical techniques commonly used for domestic animals allow wild-animal clinicians and surgeons to improve viability of threatened populations.